2020
DOI: 10.3390/pharmaceutics12111063
|View full text |Cite
|
Sign up to set email alerts
|

Combining Co-Amorphous-Based Spray Drying with Inert Carriers to Achieve Improved Bioavailability and Excellent Downstream Manufacturability

Abstract: It is crucial to improve poorly water-soluble orally administered drugs through both preclinical and therapeutic drug discovery. A co-amorphous formulation consisting of two low molecular weight (MW) molecules offers a solubility/dissolubility advantage over its crystalline form by maintaining their amorphous status. Here, we report on a co-amorphous solid dispersion (SD) system that includes inert carriers (lactose monohydrate or microcrystalline cellulose) and co-amorphous sacubitril (SAC)-valsartan (VAL) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Whilst this review will focus on the physical stability of CAMS, the chemical stability can be of interest, especially when using ball milling, which has been shown to be able to induce degradation. The reader is referred to several studies, which have investigated the chemical stability (either after preparation or after storage) [ 18 , 20 , 21 , 33 , 34 , 47 , 87 , 98 , 102 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Physical Stability Of Investigated Camsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst this review will focus on the physical stability of CAMS, the chemical stability can be of interest, especially when using ball milling, which has been shown to be able to induce degradation. The reader is referred to several studies, which have investigated the chemical stability (either after preparation or after storage) [ 18 , 20 , 21 , 33 , 34 , 47 , 87 , 98 , 102 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Physical Stability Of Investigated Camsmentioning
confidence: 99%
“…CAMS impaired the permeation of the drugs, i.e., the flux decreased by 27.8% for sacubitril and 31.0% for valsartan. [121] Hydrochlorothiazide (HCT) Arginine (L and D form) (and plus PVP)…”
Section: Permeation Testmentioning
confidence: 99%
“…The mechanism of improved dissolution and drug loading could be summarized as follows: (i) the disordered reorganization and dispersion of drug crystals leads to a reduction in particle size of the drug loaded inside the porous mannitol to the nanometer scale; (ii) corresponding improvement in wettability and dispersibility of co-treated particles; (iii) the larger pore volume of porous mannitol is conducive to the entry and penetration of the dissolution medium and improves the contact area and contact rate of the medium, thus, improving the dissolution of the drug. The applications of MCC were summarized in Table 4 [ 64 , 133 , 154 , 165 , 166 , 171 , 172 ].…”
Section: Mannitolmentioning
confidence: 99%
“…Since valsartan has a high tendency to amorphize and its crystallization is associated with many difficulties, co-amorphization is a frequently used strategy to obtain VAL formulations with an improved pharmacokinetic profile. So far, several co-amorphous solid dispersions of VAL with amino acids (L-histidine (HIS), L-arginine (ARG), Llysine (LYS)), 178 biotin (BIO) and L-tryptophan (TRP), 179 cilnidipine (CLIN), 180 nifedipine (NIFE), 181 nicotinamide (NIC), 182 and sacubitril (SACB) 183 literature. Solid dispersions of VAL with urea 184 and vanillin 185 have also been described in the literature; however, the products obtained were not fully co-amorphous or there were no XRPD studies that could confirm the fully amorphous nature of the two-component drug.…”
Section: Valsartan (Val)mentioning
confidence: 99%
“…The investigated molar ratio of VAL and NIC fully corresponded to the recommended daily dosages of VAL, and taking into account the immunomodulatory properties of NIC and its preventive role in the treatment of lung tissue damage, it was suggested that this type of co-amorphous formulation could be used in supporting treatment of COVID-19. 186 An important achievement is the development of a coamorphous formulation of VAL with SACB 183 �this combination has so far been commercially offered in the form of a co-crystal. Liu et al obtained co-amorphous VAL/SACB (molar ratio 1:1), which were additionally cospray dried with lactose monohydrate and microcrystalline cellulose.…”
Section: Valsartan (Val)mentioning
confidence: 99%